pengelolaan media sosial instagram pada konten instagram @wardahbeauty dalam membangun citra halal - fiwa, fiwasifi isyiya; arfian suryasuciramdhan; siti nurul aisyah; meiby zulfikar; rica anggraini (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
Wardah is a beauty brand produced by the company PT Paragon Technology and Innovation. Currently, the increasing competition in the beauty industry makes Wardah increasingly want to maintain its existence as the number one halal beauty product in Indonesia. Especially Wardah's image on social media, Wardah continues to build its image on content on Instagram social media. Therefore, in this research, researchers want to analyze in depth the management of @wardahbeauty Instagram content in improving and building the company's image, especially the halal label. In this research, researchers used qualitative methodology with a literature study approach model, namely to find out about content on social media Instagram @wardahbeauty in managing content on social media. The system used to collect information is done through searching, reading, listening, and taking significant notes from previous research, which comes from books and national journals. Public relations is an important element of a company which aims to ensure a good company image in the eyes of the public. The aim of this research is to find out and analyze what content is carried out on the social media Instagram @wardahbeauty. The model used is two ways symmetric. Content management is to build a halal image of Wardah products and build a good image with the public.